The impact of cannabidiol (CBD) in hyperglycemic zebrafish (Danio rerio) - Elizabeth McCarthy; Leehy Gertner; Justin Ciocirlan; Victoria P. Connaughton (PLoS ONE, 2026)
Diabetes Mellitus (DM) is a serious medical condition that impacts the lives of millions of people around the world. Complications of both micro- and macro-vascular nature occur later in life due to prolonged hyperglycemia. Hyperglycemia increases inflammation throughout the CNS and, more locally, in retina leading to the downregulation of tight-junction proteins at the blood retinal barrier and visual decline in Type 2 DM (T2DM) patients. Cannabidiol (CBD) is a cannabinoid known to lower inflammation and reduce blood glucose levels. These characteristics suggest that CBD could be used to mitigate hyperglycemic complications. To assess this, we examined if concurrent use of CBD (5 mg/L) during hyperglycemic induction would lower the risk for visual deficits in a zebrafish T2DM model. Using behavioral (optomotor response), molecular (RT-qPCR and Western Blot), and physiological (electroretinogram) techniques, we measured the response of CBD treatment on vision after a 4-week hyperglycemic period. After glucose treatment, zebrafish showed elevated blood sugar, reduced optomotor responses and compromised retinal electroretinogram recordings. Co-exposure with CBD increased performance on optomotor responses but did not significantly lower blood glucose levels. Glucose + CBD delayed photoreceptor a-wave and OFF-bipolar d-wave response times but did not restore the reduced b-wave and d-wave amplitudes observed in ERGs recorded from Glucose treated fish. Retinal homogenates from hyperglycemic fish with and without CBD co-exposure had decreased claudin-5 but increased occludin protein levels. Together, these results suggest that the CBD exposure protocol used here may broadly impact hyperglycemic sequelae but not specifically protect against microvascular complications.